Diagnosa Penyakit Ginjal Kronis Menggunakan Metode Klasifikasi Naive - Harmayani, Harmayani; Sitorus, Lamhot (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Chronic Kidney Disease is a very dangerous disease that is often not seriously considered with the effects of this disease which leads to death. More than 26 million people in the United States are not aware of their kidney disease, only 8% of them begin to realize the disease, each body must be known early whether or not the body condition / / by diagnosing it, in this study classifications will be carried out on the diagnostic data attributes Chronic kidney disease aims to simplify the process of classifying symptoms and making decisions on the diagnosis of kidney disease, this process is carried out using a data mining classification approach using the Naïve Bayes Classifier method